Growth analysis and yield performance of four potato (Solanum tuberosum L.) Varieties (Bangladesh Journal of Agricultural Research, 2018)
An experiment with four potato varieties, namely Asterix, Cardinal, Diamant and Granola was conducted at the Horticulture Research Field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during November 2013 to February 2014 to observe the behaviour of growth parameters and yield potentiality of potato. Final harvest of tuber was done at 90 DAP. LAI, CGR, RGR and NAR were not significantly influenced by the varieties. Irrespective of varieties, LAI increased progressively with time reaching a peak at 60 DAP and thereafter declined. Granola maintained the lower LAI throughout all growth stages. Numerically, the maximum CGR (19.99 g m-2 day-1) was found in Asterix at 50-60 DAP and the highest RGR (107.33 mg g-1 day-1) as well as NAR (9.54 g m-2 day-1) was recorded in Cardinal at 30-40 DAP. At 60-70 DAP, Cardinal recorded the highest TBR (84.35 g m-2 day-1) while Asterix, the highest TGR (18.54 g m-2 day-1) but Granola gave the lowest values of TBR (65.21 g m-2 day-1) and TGR (14.92 g m-2 day-1) at this growth stage. At all growth stages except 30 and 40 DAP, Diamant showed the best performance in SLA while Granola showed the lowest. The maximum yield was produced by Asterix (31.46 t/ha) closely followed by Diamant (29.91 t/ha) and Cardinal (27.27 t/ha) while the lowest yield was produced by Granola (24.82 t/ha). Granola showed the capacity of producing 95% or more of its final yield within 60 to 70 DAP. Therefore, Granola can be used as an early variety for potato cultivation.Bangladesh J. Agril. Res. 43(2): 267-280, June 2018